Infant Visual Attention and Stimulus Repetition Effects on Object Recognition. Issue 4 (20th October 2017) - Reynolds, Greg D.; Richards, John E.
Abstract : This study examined behavioral, heart rate (HR), and event‐related potential (ERP) correlates of attention and recognition memory for 4.5‐, 6‐, and 7.5‐month‐old infants ( N  = 45) during stimulus encoding. Attention was utilized as an independent variable using HR measures. The Nc ERP component associated with attention and the late slow wave (LSW) associated with recognition memory were analyzed. The 7.5‐month‐olds demonstrated a significant reduction in Nc amplitude with stimulus repetition. This reduction in Nc was not found for younger infants. Additionally, infants only demonstrated differential LSW amplitude based on stimulus type on attentive trials as defined by HR changes. These findings indicate that from 4.5 to 7.5 months, infants' attentional engagement is influenced by an increasingly broader range of stimulus characteristics.